2014
DOI: 10.2174/1874434601408010034
|View full text |Cite
|
Sign up to set email alerts
|

Making Each Other’s Daily Life: Nurse Assistants’ Experiences and Knowledge on Developing a Meaningful Daily Life in Nursing Homes

Abstract: Background:In a larger action research project, guidelines were generated for how a meaningful daily life could be developed for older persons. In this study, we focused on the nurse assistants’ (NAs) perspectives, as their knowledge is essential for a well-functioning team and quality of care. The aim was to learn from NAs’ experiences and knowledge about how to develop a meaningful daily life for older persons in nursing homes and the meaning NAs ascribe to their work.Methods:The project is based on Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The choice of respondents was based on that nurses and occupational therapists are responsible for the planning and implementation of care and rehabilitation in the current municipality and should be a part of the daily work. This could be considered a limitation, and another approach could have been to include assistant nurses as they are closest to the patient (James, Fredriksson, Wahlström, Kihlgren, & Blomberg, ). However, they are not responsible for the care and depend on nurses and occupational therapists in respect of how to carry out the care.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of respondents was based on that nurses and occupational therapists are responsible for the planning and implementation of care and rehabilitation in the current municipality and should be a part of the daily work. This could be considered a limitation, and another approach could have been to include assistant nurses as they are closest to the patient (James, Fredriksson, Wahlström, Kihlgren, & Blomberg, ). However, they are not responsible for the care and depend on nurses and occupational therapists in respect of how to carry out the care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have suggested that getting to know each other in relationships seems to promote motivation and participation Teglborg et al, 2015;Vedsegaard, Schrader, Rom, & Scheel, 2016). Through walking the path together, participation seems to ease changing processes and, in line with previous research, affirmation and acknowledgement are important in promoting participants' engagement in knowledge development and the changing of practices (James et al, 2015(James et al, , 2014Magnussen et al, 2016;Trajkovski et al, 2013b).…”
Section: Participation In Ai-a Maturing Processmentioning
confidence: 63%
“…Involving and empowering diverse groups of participants is common in AR, as can be seen in a participatory action research (PAR) study, which focused on food distribution to elderly residents living at home in Sweden (Pajalic, Persson, Skovdahl, & Westergren, 2012), and in participatory and appreciative action and reflection, which focused on meaningful daily life for older people in nursing homes, also in Sweden (James, Blomberg, Liljekvist, & Kihlgren, 2015;James, Fredriksson, Wahlström, Kihlgren, & Blomberg, 2014). A follow-up study showed that participants' fear of conflicts, lack of openness and trust, and the time period, may lead to successful cooperation becoming limited (Juthberg & Ericson-Lidman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Enrolled nurses create a meaningful daily life by being perceptive and responding accordingly to the older person. They read the older person in order to judge how the person is feeling, adapt to their daily life and share it with them [13]. The different stakeholders seem to share the same values regarding space to be yourself, habits and routines and a feeling of community to create a meaningful daily life for older persons.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on perceived meaning-in-life among older persons receiving home care, but studies from those receiving nursing home care show that it is significantly associated with the physical, emotional, social, and functional well-being quality of life dimensions [9]. What constitutes a meaningful daily life for older persons, from the perspective of the older person, the relatives and the enrolled nurses, has been reported in the action research project [10]- [13]. However there is a lack of knowledge from the leaders perspective on what constitutes a meaningful life and how it can be created for older persons receiving municipal care.…”
mentioning
confidence: 99%